A biocatalytic approach towards sustainable furanic–aliphatic polyesters1. Issue 29 (7th August 2015) - Jiang, Yi; Woortman, Albert J. J.; Alberda van Ekenstein, Gert O. R.; Loos, Katja
<x xml:space="preserve">Abstract</x> A series of sustainable furanic–aliphatic polyesters and oligoesters is successfully produced via Candida antarctica Lipase B-catalyzed polymerization of biobased dimethyl 2, 5-furandicarboxylate with various (potentially) renewable aliphatic diols.